1970
DOI: 10.3329/bjar.v34i1.5760
|View full text |Cite
|
Sign up to set email alerts
|

Performances of French bean as influenced by plant density and nitrogen application

Abstract: Field experiments with French bean comprising two varieties (BARI bush bean-1 and BARI bush bean-2), three plant densities (500 x 103, 333 x 103, and 250 x 103 plants/ha as maintained by 20 x 10, 30 x 10, and 40 x 10 cm spacings, respectively) and three levels of N (0, 60, and 120 kg/ha) were conducted at the Agricultural Research Station, Raikhali in the district of Rangamati during the winter (rabi) seasons of 2004-05 and 2005-06. BARI bush bean-1 outyielded BARI bush bean-2. The lowest plant density (250 x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
12
3
0
Order By: Relevance
“…Similarly, the results of this study are in line with the findings by Moniruzzaman et al (2009) who observed higher pod yield of French bush bean varieties in the highest plant density and the lowest pod yield with the lowest plant density. However, the study contradicts the findings of Hang et al (1993) who reported no significant effects of grains per pods of adzuki beans and dry beans due to planting density.…”
Section: Effects Of Planting Density On Number Of Pods Per Plant Numsupporting
confidence: 93%
“…Similarly, the results of this study are in line with the findings by Moniruzzaman et al (2009) who observed higher pod yield of French bush bean varieties in the highest plant density and the lowest pod yield with the lowest plant density. However, the study contradicts the findings of Hang et al (1993) who reported no significant effects of grains per pods of adzuki beans and dry beans due to planting density.…”
Section: Effects Of Planting Density On Number Of Pods Per Plant Numsupporting
confidence: 93%
“…On the other hand, the shortest pod (6.54 cm) was observed from the control (0 kg N ha -1 ). This result is in full agreement with Moniruzzaman et al (2009). He reported that pod length was significantly influenced by higher dose of nitrogen.…”
Section: Effect Of Rate Of Nitrogensupporting
confidence: 92%
“…The stimulative effect of low plant density on morphological characters, other than plant height, may be due to more exposing to solar radiation , meanwhile , prevent stem etiolating and consequently gave more branching and higher number of leaves/ plant due to large amounts of nutrients available to each plant. Obtained results are in agreement with those reported by Arisha and Bardisi (1999), Amer et al (2001), Pawar et al (2007) , , Abd El-Latif et al (2009 , Moniruzzaman et al (2009) , and Kazemi et al(2012)…”
Section: Effect Of Plant Densitysupporting
confidence: 92%
“…These results are in harmony with many investigators Arisha and Bardisi (1999) , Amer et al (2001) , Pawar et al (2007) , Mahmoud (2008) , Abd El-Latif et al (2009) , Moniruzzaman et al (2009) and Abbas (2011) . In this regard, Kazemi et al(2012) studied the effect of three plant densities (13, 16 and 22 plant/m 2 ) on snap been.…”
Section: Effect Of Plant Densitysupporting
confidence: 91%